Field study to identify requirements for smart logistics of European, US and Asian SMEs - Patrick Dallasega (2019)
© IEOM Society International. Industry 4.0 also known as the "fourth industrial revolution" will positively affect not only manufacturing processes but also the connected supply chains. Through digitization, important control information, even at an inter-company level, will become available in real-time leading to great efficiency increases. However, the increasing trend of mass customization as well as supply chains that are spread globally over the world pone specific challenges to SMEs logistics to deliver products Just-in-Time (JIT), with low costs and the right quality. Moreover, up to now mostly big companies are boosting research and development in this field letting on the track small and medium-sized enterprises (SMEs). In this paper, we present the outcomes of expert workshops to identify requirements of SMEs in the field of smart logistics management. To give a global perspective, SMEs from Central Europe, the Northern part of the United States of America as well as from Northern Thailand are presented. The paper presents an explorative set of hypothesis for requirements as well as the outline of a survey for their further validation. It summarizes the results of the first phase within the European research project "SME 4.0 - Industry 4.0 for SMEs".